Synthetic Route to Phenyl Diazenes and Pyridazinium Salts from Phenylazosulfonates - Gradl, Susanne; Köckenberger, Johannes; Oppl, Janina; Schiller, Martin; Heinrich, Markus (Journal of Organic Chemistry, 2021)
The synthesis of pyridazinium salts was achieved from readily available phenylazosulfonates in a single reaction step. The reaction proceeds via the formation of short-lived phenyldiazenes, which-owing to the strongly acidic conditions-are partially protonated. The phenyldiazenes then undergo a rapid cycloaddition to furans to give pyridazinium salts via elimination of water. The fact that the pyridazinium synthesis shows a low sensitivity toward oxygen, although phenyldiazenes occur as intermediates, can be explained by the very fast cycloaddition step and the partial protonation of the phenyldiazene.
CRIS-Team Scopus Importer:2021-06-04